2015
DOI: 10.3390/photonics2010124
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Label-Free, Distributed Bragg Grating Resonator Based Dielectric Waveguide Biosensor

Abstract: In this work, we present a resonant, dielectric waveguide device based on distributed Bragg gratings for label-free biosensing applications. The refractive index sensitive optical transducer aims at improving the performance of planar waveguide grating sensor systems with limited Q-factor and dynamic range by combing the advantages of resonant cavities, such as a multitude of resonance peaks with high finesse, with the manageable complexity of waveguide grating couplers. The general sensor concept is introduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Label-free biosensors are devices capable of quantitative assay of target analyte in a sample without using labels such as fluorophores and radioactive isotopes that need to be prelabeled on capture probes as in label-aided assays. The label-free devices that could allow real-time monitoring of time-dependent binding kinetics as well as the time-efficient and cost-effective sensing operation has led to development of a variety of technologies for clinical diagnosis of diseases, ranging from those by cyclic voltammetry techniques, impedance spectroscopy, , optical absorption spectroscopy, , and methods based on optical refractometry. …”
Section: Introductionmentioning
confidence: 99%
“…Label-free biosensors are devices capable of quantitative assay of target analyte in a sample without using labels such as fluorophores and radioactive isotopes that need to be prelabeled on capture probes as in label-aided assays. The label-free devices that could allow real-time monitoring of time-dependent binding kinetics as well as the time-efficient and cost-effective sensing operation has led to development of a variety of technologies for clinical diagnosis of diseases, ranging from those by cyclic voltammetry techniques, impedance spectroscopy, , optical absorption spectroscopy, , and methods based on optical refractometry. …”
Section: Introductionmentioning
confidence: 99%
“…Figure 8 b shows the transmission spectrum to achieve the maximum resonance shift. The measurement of the resonance shift sometimes requires lower-cost equipment and simple configuration than the measurement of the transmission extinction at a specific wavelength [ 18 ]. Our design rule and procedure also provide a large resonance shift of 0.71 nm when compared with the result in Figure 3 b.…”
Section: Discussionmentioning
confidence: 99%
“…The former advantage is due to the shift of a sharp fringe in the transmission spectrum near the stopband edge of the grating [ 14 ], and the latter is due to a solid and matured processing technology of silicon (Si)-based electrical/optical device fabrication such as the standard complementary metal-oxide-semiconductor (CMOS) process [ 16 ]. Several pieces of research successfully demonstrated the capability of Si-based grating waveguide sensor in biochemical applications [ 17 , 18 , 19 ]. We recently proposed a compact and inexpensive biochemical sensor prototype using the Si-based grating waveguide to selectively detect and quantify the multivalent binding of proteins from a monovalent binding [ 19 ], which is known to be a critical step for better understanding of fundamental mechanisms in the immune system, cancer, and thrombosis [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surface perturbation will cause change in absorption coefficient, which can be monitored in the output intensity (I) of waveguide. Optical waveguides have been extensively explored in different platforms including, but not limited to, rectangular waveguides 57 , tapered fibres 58 and more sophisticated structures such as photonic crystal waveguides (PCW) 47,[59][60][61][62][63][64][65][66][67][68] , subwavelength grating 57,69 and Bragg grating 70 . As shown in Fig.…”
Section: A Evanescent Wave Sensing: Refractive Index and Absorption V...mentioning
confidence: 99%